(untitled) (MMIT Proceedings, 2025)
The article presents detailed thoughts on the psychometric criteria of psychodiagnostic methods, its essence, application in science, the fact that the measurement of phenomena in psychology is a process consisting of determining the degree to which an object or a set of objects possesses a certain property, and if the measurement relates to a characteristic or property inherent in a person, then it is natural that this property is inherent in him to varying degrees. In addition, it is stated that a measure is a method of placing the characteristics of a person or a group of people in a continuum (scale) in relation to one of its characteristics, the measure is mainly a quantitative process, consisting in assigning numerical values to events, objects, and the rules for assigning numerical values to events determine the usefulness of the measure.